DOI: 10.18297/etd/3194
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the stories behind the numbers : a case study of maternal death surveillance and response in Goma, Democratic Republic of Congo.

Abstract: who provided insightful feedback and scholarly guidance throughout this process. They committed their time to reviewing my work and posed critical questions that challenged me to reflect more deeply. I am forever grateful to Dr. Ryan Combs, who welcomed me into his research team from the beginning of my doctoral program. His mentorship and guidance honed my skills and led to my passion for qualitative research, which was fundamental in completing this study. I also appreciate the Department of Health Promotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(45 citation statements)
references
References 156 publications
0
45
0
Order By: Relevance
“…This learning, and the review process itself, were reported to make health workers more vigilant in their daily practice, because they knew that if a patient died, their actions and records would be reviewed. 44 , 53 , 75 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This learning, and the review process itself, were reported to make health workers more vigilant in their daily practice, because they knew that if a patient died, their actions and records would be reviewed. 44 , 53 , 75 …”
Section: Resultsmentioning
confidence: 99%
“…3 ), where people feel safe to honestly report deaths, disclose accurate information and openly discuss the cases, including any mistakes in their management. 47 , 53 , 56 , 74 Learning environments assure confidentiality, anonymity and separation from blame or any disciplinary process. Although several respondents recommended legal protection at the national level to prevent data from maternal and perinatal death surveillance and response being used in litigation, only South Africa had enacted this protection which “has been ratified by relevant judicial bodies.” 81 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations